NIR-responsive NaYF4:Yb, Er, Gd fluorescent upconversion nanorods for the highly sensitive detection of blood fingerprints. (November 2016) - Li, Bai-Yu; Zhang, Xiao-Lin; Zhang, Ling-Yu; Wang, Ting-Ting; Li, Lu; Wang, Chun-Gang; Su, Zhong-Min
Abstract: In this paper, the NaYF4 :Yb, Er, Gd fluorescent upconversion nanorods (UCNRs) were successfully employed as a promising fluorescent label for the detection of blood fingerprints with high sensitivity, low background, high efficiency, and low toxicity on a range of substrates including non-infiltrating materials (glass, ceramic tile, aluminium foil, stainless steel sheet, coin and marble), and infiltrating materials (magazine cover and train ticket). To assess the efficiency of this approach, comparisons were performed with Acid Yellow 7 (AY7, an effective blood reagent) on above-mentioned eight substrates. The fingerprints were cut in halves and the halves treated separately with UCNRs and AY7. The results manifested that UCNRs were superior to AY7 on all test substrates. This work shows that UCNRs are a versatile fluorescent label for the detection of blood fingerprints in criminal science for individual identification. Graphical abstract: NaYF4 :Yb, Er, Gd upconversion nanorods were employed as a promising fluorescent label for the detection of blood fingerprints with high sensitivity, low background, high efficiency and low toxicity on a range of substrates including non-infiltrating materials (glass, ceramic tile, aluminium foil, stainless steel sheet, coin and marble), and infiltrating materials (magazine cover and train ticket). Highlights: Upconversion nanorods are used for blood fingerprints detection. They show high sensitivity, low background, high efficiency and low toxicity. They are superior to Acid Yellow 7 (a blood-sensitive reagent) on all substrates. The whole procedure is facile and convenient to use at the scene of the crime.